1990
DOI: 10.1103/physrevd.42.437
|View full text |Cite
|
Sign up to set email alerts
|

Exact Faraday rotation in the cylindrical Einstein-Maxwell waves

Abstract: We obtain the exact behavior of the cross-polarized cylindrical Einstein-Maxwell waves that generalizes the well-known Einstein-Rosen waves. In the presence of the second mode of polarization the outgoing waves interact with the incoming ones to exhibit an analogous effect of the Faraday rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…All the results obtained so far are consistent with the hoop conjecture [302]: black holes with horizons form when and only when a mass M gets compacted into a region whose circumference is C 4πM in every direction 13 .…”
Section: The Hoop Conjecture and Critical Collapsesupporting
confidence: 85%
See 1 more Smart Citation
“…All the results obtained so far are consistent with the hoop conjecture [302]: black holes with horizons form when and only when a mass M gets compacted into a region whose circumference is C 4πM in every direction 13 .…”
Section: The Hoop Conjecture and Critical Collapsesupporting
confidence: 85%
“…It was found that the polarizations of one GW can be rotated by the other, due to their nonlinear interaction, an analogue of the electromagnetic Faraday rotation. Since then, detailed studies of gravitational Faraday rotation have been carried out in various situations, including Einstein-Maxwell waves [13], rotating cylindrical GWs [259], and more recently, cylindrical gravitational soliton waves [305].…”
Section: Introductionmentioning
confidence: 99%
“…The main feature on which we concentrate here is the rotation of em polarization vector known as the Faraday effect. Such rotation has been introduced also for the GWs [5][6][7][8]; however, its detection is hampered by the challenge of detecting GWs themselves.…”
Section: Introductionmentioning
confidence: 99%